Long-Term Outcomes After Extensor Carpi Ulnaris Subsheath Reconstruction With Extensor Retinaculum. Issue 1 (March 2020) - Verhiel, Svenna H.W.L.; Özkan, Sezai; Chen, Neal C.; Jupiter, Jesse B.
Abstract : This study assessed the long-term outcomes and complications of patients that underwent operative treatment for extensor carpi ulnaris subluxation. Fifteen patients underwent extensor carpi ulnaris subsheath reconstruction at a median of 5.9 weeks nonoperative treatment interval (interquartile range: 2.4 to 13). Reconstruction consisted of using the extensor retinaculum as a sling reconstruction. We found that about 1 in 3 patients had a complication or reoperation. At a median of 8 years follow-up, many patients had some residual symptoms, but in general, most patients were satisfied.